Economia solidária e trabalho coletivo : Um olhar sobre a Cooperativa do Riachão no Norte de Minas Gerais - Brasil - Silva, Queite Marrone Soares da (2014)
It is intended to discuss the prospect of collective work in solidarity economy, from experiences with those of the Cooperative Riachao workers, located in a rural community in the municipality of Montes Claros, Minas Gerais / Brazil, this approximately 240 farming families extractive are benefited with the generation of jobs and income through initiatives grounded in associations, cooperatives and collectives. Among the 80 to 90 years, appeared inBrazil experiences of solidarity, resulting economy of the labor market crisis and rising unemployment, and an important response to the workers in relation to changes in the world of work. It is grounded in the organization of groups of workers, by way of solidarity, community, cooperation, and self-management reactions. In this sense, we intend to present the achievements, challenges and dilemmas of workers COOPERIACHAO, around a project that aims at empowerment of social actors and social transformation of the subject